Personal Statement to Personal Physician: Bait and Switch? - Breen, James O. (The Hastings Center report, 2014)
In our family medicine program, applicants' personal statements largely speak to the value of trusting, continuous doctor-patient relationships. They give poignant examples of patient interactions that have allowed the applicants to experience the privilege of the intimacy with which patients relate to their doctors. Whatever their true motivations for choosing family medicine, the relational values expressed in the personal statement are the ones we celebrate and incentivize in the residency selection process. However, after donning their freshly pressed white coats, new interns in family medicine hear different definitions of value applied to their chosen specialty.